Pattern of tuberculosis among tribal population of Central India with special reference to cartridge based nucleic acid amplification test as diagnostic tool: a descriptive study at tertiary care hospital - Gajbhiye, Swati B.; Madkey, Madhavi V.; Gedam, Dilip S. (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculosis (TB) kills close to half a million Indians every year. Lack of reliable rapid diagnostic techniques for TB hampers timely diagnosis and leads to continued disease transmission, causing significant morbidity and mortality. The potential of newly recommended CBNAAT in TB and MDR-TB detection has been underutilized in our area due to lack of awareness regarding the same. Hence we utilized this rapid, logistically simplified test to study the pattern of tuberculosis among tribal population of Central India. Methods: Descriptive study of suspected TB patients in tertiary care centre from March 2016 to March 2019. Appropriate specimens from suspected TB patients were collected and subjected to CBNAAT and AFB smear to study the pattern of TB and Rifampicin- Resistant(RR) TB in our area. Results: CBNAAT detected overall 27% MTB cases; 27.72 % Pulmonary-TB cases as against smear positivity rate of 20.73% whereas 12.74% Extra-pulmonary-TB (EPTB) cases as against smear positivity rate of 1.59%.Overall 94.91% were RiF Sensitive( RS-TB) and 4.58% were RR-TB. Of the 57 (4.16%) HIV-TB coinfected cases; 96.49% were RS-TB and 5.26% were RR-TB. Co-infected patients have high incidence of EPTB(21.05%) involvement with RR-TB 3.50%. Among EPTB cases; lymph node aspirate and pus provided highest CBNAAT positive cases and almost 90.62% EPTB specimens were RS-TB . Conclusions: Availability of new diagnostic services has increased early identification of TB and RR-TB. Awareness among physicians regarding diagnostic utility of CBNAAT should be further increased as early identification of possible MDR cases is key to reducing community transmission and treatment initiation, particularly in high-burden, resource-limited settings.